Nanotechnology in Eco-Efficient Construction 2013
DOI: 10.1533/9780857098832.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for high performance concrete (HPC)

Abstract: According to the 2011 ERMCO statistics, only 11% of the production of ready-mixed concrete relates to the high performance concrete (HPC) target. This percentage has remained unchanged since at least 2001 and appears a strange choice on the part of the construction industry, as HPC offers several advantages over normal-strength concrete, specifi cally those of high strength and durability. It allows for concrete structures requiring less steel reinforcement and offers a longer serviceable life, both of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In recent years, a group of researchers was working on the utility of LC 3 as it is economical and environment friendly. In LC 3 , calcined clay is present, which is a pozzolanic material and forms C-(A)-S-H and AFm phases similar to that of OPC during hydration. In the presence of limestone, C3A reacts to give monocarboaluminate (Mc) and hemicarboaluminate (Hc).…”
Section: Lc 3 In Presence Of Nano Silicamentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a group of researchers was working on the utility of LC 3 as it is economical and environment friendly. In LC 3 , calcined clay is present, which is a pozzolanic material and forms C-(A)-S-H and AFm phases similar to that of OPC during hydration. In the presence of limestone, C3A reacts to give monocarboaluminate (Mc) and hemicarboaluminate (Hc).…”
Section: Lc 3 In Presence Of Nano Silicamentioning
confidence: 99%
“…Portland cement (OPC), a main binding component in concrete, consumes lot of raw materials, energy and emits huge amount of CO2 gas during its production. Concrete, the most important construction materials, is produced at about 27.3 billion tonnes in 2015 [1][2][3][4][5][6][7]. It is expected that OPC production may increase by nearly 200% by 2050 with 6,000 million tonnes [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a balance is required to continue building without significant negative effects on the environment. (5) reported that as much as 50 % of reinforced steel use could be reduced by increasing concrete's compressive strength. Durable and high strength concrete is the main concern in future production as far material and eco-efficiencies are concerned.…”
Section: Introductionmentioning
confidence: 99%